On the assessment of regional intellectual and innovation activities based on measurement theory methods and panel data regression analysis. (17th June 2019) - Dubina, Igor N.; Mkrtchyan, Gagik M.; Ostaschenko, Tatiana V.; Baitenizov, Daniyar T.
This paper presents the authors' approach to the assessment and analysis of regional intellectual and innovation activities with such main components as intellectual and innovation potential, climate and capital. The validity and reliability of the developed indexes were tested on the basis of a set of economic and statistical data characterising the development of 12 Russian regions for 15 years with methods of factor analysis, correlation and regression analysis and measurement theory. This research demonstrates a stable and statistically significant relationship between economic development of the regions and their intellectual and innovation activities. The panel data regression analysis of the aggregated indexes and the indicators of regional economic development proved the authors' hypothesis of the mutual influence of regional innovation and economic development with a deferred (time lag) effect.